The impact of individual investment behavior for retirement welfare: Evidence from the United States and Germany - Thomas Post; Helmut Gründl; Joan Schmit; Anja Zimmer (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
Much of the industrialized world is undergoing a significant demographic shift, placing strain on public pension systems. Policymakers are responding with pension system reforms that put more weight on privately managed retirement funds. One concern with these changes is the effect on individual welfare if individuals invest suboptimally. Using micro-level data from the United States and Germany, we compare the optimal expected lifetime utility computed using a realistically calibrated model with the actual utility as reflected in empirical asset allocation choices. Through this analysis, we are able to identify the population subgroups with relatively large welfare losses. Our results should be helpful to public policymakers in designing programs to improve the performance of privately organized retirement systems.
Keywords: D14; D91; G11; G28; I31; 330; Asset allocation; retirement welfare; pension reform; Private Rentenversicherung; Anlageverhalten; Erwartungsnutzen; Lebensverlauf; Wohlfahrtseffekt; Deutschland; USA